The Rare Codon AGA Is Involved in Regulation of Pyoluteorin Biosynthesis in Pseudomonas protegens Pf-5 - Yan, Qing; Philmus, Benjamin; Hesse, Cedar; Kohen, Max; Chang, Jeff H.; Loper, Joyce E. (Frontiers in Microbiology, 2016)
The soil bacterium Pseudomonas protegens Pf-5 can colonize root and seed surfaces of many plants, protecting them from infection by plant pathogenic fungi and oomycetes. This capacity to suppress disease is attributed to Pf-5’s production of a large spectrum of antibiotics, which is controlled by complex regulatory circuits operating at the transcriptional and post-transcriptional levels. In this study, we analyzed the genomic sequence of Pf-5 for codon usage patterns and observed that the six rarest codons in the genome are present in all seven known antibiotic biosynthesis gene clusters. In particular, there is an abundance of rare codons in pltR, which encodes a member of the LysR transcriptional regulator family that controls the expression of pyoluteorin biosynthetic genes. To test the hypothesis that rare codons in pltR influence pyoluteorin production, we generated a derivative of Pf-5 in which 23 types of rare codons in pltR were substituted with synonymous preferred codons. The resultant mutant produced pyoluteorin at levels 15 times higher than that of the wild-type Pf-5. Accordingly, the promoter activity of the pyoluteorin biosynthetic gene pltL was 20 times higher in the codon-modified stain than in the wild-type. pltR has six AGA codons, which is the rarest codon in the Pf-5 genome. Substitution of all six AGA codons with preferred Arg codons resulted in a variant of pltR that conferred increased pyoluteorin production and pltL promoter activity. Furthermore, overexpression of tRNAArgUCU, the cognate tRNA for the AGA codon, significantly increased pyoluteorin production by Pf-5. A bias in codon usage has been linked to the regulation of many phenotypes in eukaryotes and prokaryotes but, to our knowledge, this is the first example of the role of a rare codon in the regulation of antibiotic production by a Gram-negative bacterium.